Rationality in Perception in Medieval Philosophy
1 online resource
Keywords: How we come to know the external world has intrigued thinkers throughout the history of philosophy. Medieval philosophers understood that a theory of perception requires an account of the categorization of sensory information: to perceive things as being dangerous or beneficial and even as being individuals that belong to certain kinds (e.g., ‘this is a dog’). A key question is whether this requires the intervention of rational cognitive capacities, cooperating with sensory ones in normal instances of perception. The contributions to this volume investigate how thinkers from the thirteenth and fourteenth centuries answer this and other related questions about human perception. Contributors are Fabrizio Amerini, Joël Biard, Véronique Decaix, Christian Kny, Lydia Schumacher, José Filipe Silva, and Jörg Alejandro Tellkamp.